2022
DOI: 10.21508/1027-4065-2022-67-5-170-176
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory indicators of nutritional status in children with cerebral palsy

Abstract: Children with cerebral palsy are at high risk of developing nutritional disorders: malnutrition, osteopenia, micronutrient deficiency. This is facilitated by motor disorders, restriction of actual nutrition, the presence of concomitant drug therapy, and metabolic features.Purpose. The study aims at evaluation of laboratory markers of nutritional status in children with cerebral palsy.Material and methods: for a comprehensive assessment of nutritional status disorders, a cross-sectional analytical study of 175 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 9 publications
2
3
1
Order By: Relevance
“…In the same study, Carman et al reported that children with CP exhibited low levels of zinc, vitamin A, phosphorus, and manganese [22]. In another study conducted on patients with CP, 14.5% of patients exhibited phosphorus de ciency [23]. In accordance with the ndings of previous studies, our investigation revealed hypophosphatemia in 18.3% of patients.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the same study, Carman et al reported that children with CP exhibited low levels of zinc, vitamin A, phosphorus, and manganese [22]. In another study conducted on patients with CP, 14.5% of patients exhibited phosphorus de ciency [23]. In accordance with the ndings of previous studies, our investigation revealed hypophosphatemia in 18.3% of patients.…”
Section: Discussionsupporting
confidence: 90%
“…The vitamin B12 de ciency observed in our patient was lower than that observed in other studies (1.1%) [8, 23,32]. In addition, along with iron parameters, vitamin B12 was the only vitamin that did not correlate with age.…”
Section: Discussioncontrasting
confidence: 69%
See 3 more Smart Citations